It girl : the life and legacy of Jane Birkin - Meltzer, Marisa, 1977- (Atria Books, an imprint of Simon & Schuster, LLC, 2025)
"Jane Birkin was synonymous with chic. Her effortless style and artistic legacy have been immortalized through her music and film career. And, of course, she was the inspiration behind one of the world's most coveted bags, the Hermès Birkin. But who was the real woman behind the it girl? Now, New York Times bestselling author Marisa Meltzer sheds new light on Birkin's enigmatic life and explores her profound influence on generations in a rigorously reported biography unlike any other. It Girl paints a vivid portrait of Birkin and her profound legacy, from her early years in 1960s London to her rise as a beloved celebrity in France, detailing personal challenges, her relationships with creative powerhouses, and the duality of her public and private selves. Based on interviews and deep archival research, Meltzer reveals the nuances of Birkin's character: her famously tempestuous romantic relationships, life with her three famous daughters, and the creative energy that drove her. It Girl tells the story of her indelible impact on femininity and style, and how what we think of as French girl style grew from her. Far from being just a muse, Birkin is at last given her well-deserved due." --